EFFECT OF DIFFERENT GONADOTROPINON IN VITRO ON DEVELOPMENT OF IMMATURE CAPRINE OOCYTES - KOUAMO, J; KHARCHE, S D (The Indian Journal of Animal Reproduction, 2023)
The objective of the present study is to compare the embryo development from caprine oocytes matured in vitro in a medium supplemented with PMSG alone or in combination with hCG. Cumulus oocyte complexes (573) were matured in two treatment groups. Group 1 (n=377) COCs were matured inTCM-199 medium supplemented with 20 IU/ml PMSG. Group 2 (n=196) COCs were matured inTCM-199 medium supplemented with 20 IU/ml PMSG+20 IU/ml hCG. After 27h of maturation, oocytes were fertilized in mTALP and cultured in mCR2aa medium. The maturation rate in groups 1 and 2 were 88.63% and 91.78% respectively. Similarly, cleavage rates, morula and blastocyst production in groups 1 and 2 were 47 .13, 20.00, 10.00 and 43.21, 22.85, 7.14% respectively. The results indicated that oocytes matured with 20IU/ml PMSG had a good cytoplasmic maturation that allows normal embryo development up to blastocyst stagewithout addition of hCG. Thus, PMSG at 20IU/ml in maturation medium can be used for in vitro embryo production.